Carbon supported NiRu nanoparticles as effective hydrogen evolution catalysts for anion exchange membrane water electrolyzers - Ruck, Stephan; Körner, Andreas; Hutzler, A.; Bierling, Markus; Gonzalez, J.; Qu, W.; Bock, C.; Thiele, Simon; Peach, R.; Pham, C. (JPhys Energy, 2022)
Establishing anion exchange membrane water electrolysis (AEMWE) as a new technology for efficient hydrogen production requires cost-effective and high-performance catalyst materials. Here, we report the synthesis and comprehensive characterization of carbon supported NiRu alloy nanoparticles as a cost-effective hydrogen evolution reaction catalyst for AEMWEs. Different NiRu catalysts were synthesized using a facile and scalable impregnation method. Half-cell results showed the 'NiRu' catalyst with ca. 10 wt.% Ru to exhibit an increased noble metal mass activity and slightly decreased Tafel slope compared to a commercial Pt/C catalyst with 60 wt.% Pt. Further, we report the application of NiRu/C as a cathodic catalyst in AEMWE full cell for the first time. In full cell tests, the synthesized catalysts exhibit 2 A cm(-2) at 1.95 V with a low loading of 0.1 mg(PGM) cm(-2) at the cathode.
CRIS-Team WoS Importer:2022-10-28

Communication-Proving the Importance of Pt-Interlayer Position in PEMWE Membranes for the Effective Reduction of the Anodic Hydrogen Content - Martin, Agate; Abbas, Dunia; Trinke, Patrick; Boehm, Thomas; Bierling, Markus; Bensmann, Boris; Thiele, Simon; Hanke-Rauschenbach, Richard (Journal of The Electrochemical Society, 2021)
Gas crossover through the membrane poses a significant challenge to proton exchange membrane water electrolysers. This work investigates the influence of the position of platinum-based recombination interlayers integrated in the membrane on the anodic hydrogen in oxygen content. The results show that all interlayer positions reduce the anodic hydrogen content without performance losses compared to the reference without interlayer. However, an interlayer positioned closer to the anode is more effective than closer to the cathode. Further, the effect of the interlayer is more pronounced with increasing anode pressure.
CRIS-Team WoS Importer:2021-10-08

Digital Twin of a Hierarchical CO2 Electrolyzer Gas Diffusion Electrode - Mclaughlin, David; Bierling, Markus; Mayerhöfer, Britta; Schmid, Guenter; Thiele, Simon (Advanced Functional Materials, 2022)
The electrochemical reduction of CO2 provides a pathway to a sustainable carbon cycle, allowing for the production of hydrocarbons critical for both chemical industry and mobility. Major engineering challenges need to be met in order to achieve efficient and large-scale CO2 electrolysis. One central challenge is to find the optimum structure for the gas diffusion electrode at the heart of the electrolyzer. An optimum structure will achieve higher conversion efficiencies, lifetime, and product selectivity at lower cost. Critical structural properties of the electrode span the scale from nanometers to millimeters. To rationalize the optimization process, it behooves us to obtain a fully resolved multi-scale model of the electrode. This digital twin, produced by bridging scale and employing multiple imaging methods, enables the digital study, simulation, and modification of the structure of the electrode. The model is used to simulate the transport processes vital to the functioning of the electrode thus further advancing the digital twin. Subsequently, it is explored how changes to the structure affect the predicted transport properties. The digital twin presented is only supposed to be the kernel and will be complemented by numerous future works.
CRIS-Team WoS Importer:2023-01-20

Dissolution of WO3 modified with IrOx overlayers during photoelectrochemical water splitting - Jenewein, Ken; Knöppel, Julius; Hofer, André; Kormanyos, Attila; Mayerhöfer, Britta; Speck, Florian; Bierling, Markus; Thiele, Simon; Bachmann, Julien; Cherevko, Serhiy (SusMat, 2023)
WO3, an abundant transition metal semiconductor, is one of the most discussed materials to be used as a photoanode in photoelectrochemical water-splitting devices. The photoelectrochemical properties, such as photoactivity and selectivity of WO3 in different electrolytes, are already well understood. However, the understanding of stability, one of the most important properties for utilization in a commercial device, is still in the early stages. In this work, a photoelectrochemical scanning flow cell coupled to an inductively coupled plasma mass spectrometer is applied to determine the influence of co-catalyst overlayers on photoanode stability. Spray-coated WO3 photoanodes are used as a model system. Iridium is applied to the electrodes by atomic layer deposition in controlled layer thickness, as determined by ellipsometry and x-ray photoelectron spectroscopy. Photoactivity of the iridium-modified WO3 photoanodes decreases with increasing iridium layer thickness. Partial blocking of the WO3 surface by iridium is proposed as the main cause of the decreased photoelectrochemical performance. On the other hand, the stability of WO3 is notably increased even in the presence of the thinnest investigated iridium overlayer. Based on our findings, we provide a set of strategies to synthesize nanocomposite photoelectrodes simultaneously possessing high photoelectrochemical activity and photostability.<br

In Search of Lost Iridium: Quantification of Anode Catalyst Layer Dissolution in Proton Exchange Membrane Water Electrolyzers - Milosevic, Maja; Böhm, Thomas; Körner, Andreas; Bierling, Markus; Winkelmann, Leonard; Ehelebe, Konrad; Hutzler, Andreas; Suermann, Michel; Thiele, Simon; Cherevko, Serhiy (ACS Energy Letters, 2023)
Understanding catalyst dissolution pathways in proton exchange membrane water electrolyzers is paramount for developing mitigation strategies aiming toward higher durability and lower catalyst loadings. To this end, Ir dissolution has been extensively studied using aqueous model systems but not in real devices. Aiming to bridge this knowledge gap, we use a metal-free water electrolysis setup to determine the mass balance of the dissolved Ir in an electrolyzer when applying a protocol mimicking intermittent operation. We find that the main Ir sinks are the cathode catalyst layer and the membrane, while Ir dissolution into the water lines is significantly lower. Although reproducible estimation of Ir present in the membrane is challenging, quantification of Ir within the cathode is reliable and efficient. This new finding implies that tracking Ir present in the cathode can be used to estimate anode catalyst stability, thus accelerating catalyst development and operational parameters optimization.
CRIS-Team Scopus Importer:2023-07-07

IrO2 coated TiO2 core-shell microparticles advance performance of low loading proton exchange membrane water electrolyzers - Pham, Chuyen Van; Bühler, Melanie; Knöppel, Julius; Bierling, Markus; Seeberger, Dominik; Escalera-López, Daniel; Mayrhofer, Karl; Cherevko, Serhiy; Thiele, Simon; Thiele, Simon (Applied Catalysis B-Environmental, 2020)
Herein we present novel IrO2 coated TiO2 core-shell microparticles (IrO2@TiO2) as an oxygen evolution reaction catalyst. We compare the IrO2@TiO2 catalyst to commercial TiO2 supported IrO2 catalyst (IrO2/TiO2) and pure IrO2 catalyst powder. A stability analysis via on-line inductively coupled plasma mass spectrometry based on the S-number, a descriptor considering both energy efficiency and catalyst utilization efficiency, shows that the IrO2@TiO2 catalyst shows high potential for practical applications. This was further confirmed by full-cell tests showing superior performance of the IrO2@TiO2 catalyst with moderate and low loadings of 1.2 mgIr cm−2 and 0.4 mgIr cm−2, respectively. The core-shell catalyst is synthesized via facile route suitable for large quantities. Moreover, stable inks from the synthesized catalyst powder make this system appealing for large scale manufacturing of cells. Given the facile synthesis route, high activity, and good stability, the IrO2@TiO2 catalyst is potentially suitable for industry proton exchange membrane water electrolysis application.
CRIS-Team Scopus Importer:2020-02-28
Keywords: Core shell catalyst; Iridium oxide catalyst; Oxygen evolution reaction; Proton exchange membrane; Water electrolysis

On the Correlation between the Oxygen in Hydrogen Content and the Catalytic Activity of Cathode Catalysts in PEM Water Electrolysis - Martin, Agate; Trinke, Patrick; Van Pham, Chuyen; Buehler, Melanie; Bierling, Markus; Holzapfel, Peter K. R.; Bensmann, Boris; Thiele, Simon; Hanke-Rauschenbach, Richard (Journal of The Electrochemical Society, 2021)
Altogether five platinum group metal (PGM) and PGM-free cathode catalysts were investigated in full PEM water electrolysis cells regarding their polarisation behaviour and their hydrogen and oxygen recombination properties. It was shown that the recombination activity of permeated oxygen and evolved hydrogen within the cathodic catalyst layer correlates with the activity of the oxygen reduction reaction (ORR) which was determined ex situ with linear sweep voltammetry. We found that the investigated PGM-free cathode catalysts had a low activity for the ORR resulting in higher measurable oxygen in hydrogen volume fractions compared to the PGM catalysts, which are more active for the ORR. Out of the three investigated PGM-free catalysts, only one commercially available material based on a Ti suboxide showed a similar good polarisation behaviour as the state of the art cathode catalyst platinum, while its recombination activity was the lowest of all catalysts. In addition to the recombination of hydrogen and oxygen on the electrocatalysts, we found that the prevalent carbon-based cathodic porous transport layers (PTL) also offer catalytically active recombination sites. In comparison to an inactive PTL, the measurable oxygen flux using carbon-based PTLs was lower and the recombination was enhanced by microporous coatings with high surface areas.
CRIS-Team WoS Importer:2021-12-03

On the limitations in assessing stability of oxygen evolution catalysts using aqueous model electrochemical cells - Knöppel, Julius; Möckl, Maximilian; Escalera-López, Daniel; Stojanovski, Kevin; Bierling, Markus; Böhm, Thomas; Thiele, Simon; Rzepka, Matthias; Cherevko, Serhiy (Nature Communications, 2021)
Recent research indicates a severe discrepancy between oxygen evolution reaction catalysts dissolution in aqueous model systems and membrane electrode assemblies. This questions the relevance of the widespread aqueous testing for real world application. In this study, we aim to determine the processes responsible for the dissolution discrepancy. Experimental parameters known to diverge in both systems are individually tested for their influence on dissolution of an Ir-based catalyst. Ir dissolution is studied in an aqueous model system, a scanning flow cell coupled to an inductively coupled plasma mass spectrometer. Real dissolution rates of the Ir OER catalyst in membrane electrode assemblies are measured with a specifically developed, dedicated setup. Overestimated acidity in the anode catalyst layer and stabilization over time in real devices are proposed as main contributors to the dissolution discrepancy. The results shown here lead to clear guidelines for anode electrocatalyst testing parameters to resemble realistic electrolyzer operating conditions.
CRIS-Team Scopus Importer:2021-04-30

Optimization of anodic porous transport electrodes for proton exchange membrane water electrolyzers - Bühler, Melanie; Hegge, Friedemann; Holzapfel, Peter; Bierling, Markus; Suermann, Michel; Vierrath, Severin; Thiele, Simon (Journal of Materials Chemistry A, 2019)
In this study we investigate the potential of porous transport electrode (PTE) based membrane electrode assemblies (MEAs) for proton exchange membrane water electrolysis. The focus is on the overpotential determining anodic PTE for the oxygen evolution reaction. The influences of catalyst loading, ionomer content and porous titanium substrate on the polarization behavior are analyzed. The comparison of a porous fiber-sintered substrate with a powder-sintered substrate shows no significant differences in the kinetic and mass transport regions. Ohmic losses, however, are lower for fiber PTEs above a catalyst loading of 1.0 mgIrO2 cm-2. Variations of the Nafion content in the catalyst layer reveal changes of mass transport and ohmic losses and have an influence on the reproducibility. Varying the noble metal loading and therefore the thickness of the applied catalyst layer influences the kinetic region and ohmic resistance of the MEAs. The best compromise between reproducibility and performance is found for a loading of 1.4 mgIrO2 cm-2 and 9 wt% Nafion. The stable operation of the aforementioned PTE is shown in a 200 h durability test at 2 A cm-2.
CRIS-Team Scopus Importer:2019-12-17

Photocorrosion of WO3 Photoanodes in Different Electrolytes - Knöppel, Julius; Kormanyos, Attila; Mayerhöfer, Britta; Hofer, André; Bierling, Markus; Bachmann, Julien; Thiele, Simon; Cherevko, Serhiy (ACS Physical Chemistry Au, 2021)
Photocorrosion of an n-type semiconductor is anticipated to be unfavorable if its decomposition potential is situated below its valence band-edge position. Tungsten trioxide (WO3) is generally considered as a stable photoanode for different photoelectrochemical (PEC) applications. Such oversimplified considerations ignore reactions with electrolytes added to the solvent. Moreover, kinetic effects are neglected. The fallacy of such approaches has been demonstrated in our previous study dealing with WO3 instability in H2SO4. In this work, in order to understand parameters influencing WO3 photocorrosion and to identify more suitable reaction environments, H2SO4, HClO4, HNO3, CH3O3SH, as electrolytes are considered. Model WO3 thin films are fabricated with a spray-coating process. Photoactivity of the samples is determined with a photoelectrochemical scanning flow cell. Photostability is measured in real time by coupling an inductively coupled plasma mass spectrometer to the scanning flow cell to determine the photoanode dissolution products. It is found that the photoactivity of the WO3 films increases as HNO3 < HClO4 ≈ H2SO4 < CH3O3SH, whereas the photostability exhibits the opposite trend. The differences observed in photocorrosion are explained considering stability of the electrolytes toward decomposition. This work demonstrates that electrolytes and their reactive intermediates clearly influence the photostability of photoelectrodes. Thus, the careful selection of the photoelectrode/electrolyte combination is of crucial importance in the design of a stable photoelectrochemical water-splitting device.
Keywords: Photocorrosion; Tungsten oxide; Photostability; Water splitting; Electrode kinetics

Platinum Dissolution in Realistic Fuel Cell Catalyst Layers - Ehelebe, Konrad; Knöppel, Julius; Bierling, Markus; Mayerhöfer, Britta; Böhm, Thomas; Kulyk, Nadiia; Thiele, Simon; Mayrhofer, Karl; Cherevko, Serhiy (Angewandte Chemie International Edition, 2021)
Pt dissolution has already been intensively studied in aqueous model systems and many mechanistic insights have been gained. Nevertheless, transfer of new knowledge to real-world fuel cell systems is still a significant challenge. To close this gap, we present a novel in situ method combining a gas diffusion electrode (GDE) half-cell with inductively coupled plasma mass spectrometry (ICP-MS). With this setup, Pt dissolution in realistic catalyst layers and the transport of dissolved Pt species through Nafion membranes were evaluated directly. We observed that 1) specific Pt dissolution increased significantly with decreasing Pt loading, 2) in comparison to experiments on aqueous model systems with flow cells, the measured dissolution in GDE experiments was considerably lower, and 3) by adding a membrane onto the catalyst layer, Pt dissolution was reduced even further. All these phenomena are attributed to the varying mass transport conditions of dissolved Pt species, influencing re-deposition and equilibrium potential.
CRIS-Team WoS Importer:2021-03-12

Tomographic Reconstruction and Analysis of a Silver CO2 Reduction Cathode - Mclaughlin, David; Bierling, Markus; Moroni, Riko; Vogl, Christoph; Schmid, Guenter; Thiele, Simon (Advanced Energy Materials, 2020)
Tomographic reconstruction has been well established as a valuable tool in the analysis of polymer electrolyte fuel cell (PEMFC) electrodes. While forays have been made into applying it to polymer electrolyte water electrolyzer (PEMWE) electrodes, CO2 electrolyzer electrodes are still new ground. Here a tomographic analysis of an electrochemical CO2 reduction gas diffusion electrode by means of focused ion beam scanning electron microscope tomography is presented. The reconstruction shows a porosity of 68%. While most of the porosity is on the nanoscale, a broad tail of micropores is observed in the distribution. The spatial distribution of the pores is nonuniform. The large pores are concentrated in the center of the layer in the through-plane direction. From the reconstruction, an effective diffusivity factor of 0.5 for the catalyst layer is calculated. The Knudsen number of 0.19 obtained from the later shows that the diffusion is mostly in the bulk regime. Flooding of the catalyst layer is likely to decrease the effective diffusivity factor substantially.
CRIS-Team Scopus Importer:2020-04-17
Keywords: CO; FIB-SEM; gas diffusion electrodes; power-to-X technology; tomography